Naming the parts: a case-study of a gender equality initiative with academic women. Issue 5 (6th July 2015) - O Grada, Aifric; Ní Laoire, Caitríona; Linehan, Carol; Boylan, Geraldine; Connolly, Linda
Abstract : Purpose: – This paper aims to seek to contribute to current debates about the effectiveness of different types of gender equality interventions in the academic context. This paper presents an argument for the need to move beyond an individual-structural dichotomy in how such interventions are perceived. Design/methodology/approach: – The paper draws on an action-research case-study, the Through the Glass Ceiling project, to challenge the idea that "individual"/single-actor interventions serve only to reinforce underlying inequalities by attempting to "fix the women". Findings: – It is suggested that actions that support women in their careers have the potential to achieve a degree of transformation at individual, cultural and structural levels when such actions are designed with an understanding of how individuals embody the gendered and gendering social structures and values that are constantly being produced and reproduced within society and academia. The case study highlights the benefits of supporting individuals as gendered actors in gendering institutions and of facilitating the development of critical gender awareness, suggesting that such interventions are most effective when undertaken as part of an integrated institutional equality agenda. Originality/value: – By calling attention to the ongoing mutual construction of actors and practices in organizations, this paper seeks to make both a conceptual contribution to how we understand the (re)production and potential transformation of gender relations in academia and to influence wider policy dialogues on diversity at work.